The Ukrainian-Polish Seminars - Liashenko, V.; Chebotarov, Iе. (Економічний вісник Донбасу, 2019)
The Institute of Industrial Economics of the National
Academy of Sciences of Ukraine (Kyiv) have a
good tradition of seminars with polish colleagues from
Universities of Poznan, Lodz and Zabje.
On December 2-3, 2019, on the basis of the Institute
of Industrial Economics of the National Academy
of Sciences of Ukraine (Kyiv), the Ukrainian-Polish
seminar “Reforms of self-government and education
systems in Poland: problems and implementation mechanisms
in Ukraine” was traditionally successfully
held.